1995
DOI: 10.1200/jco.1995.13.5.1188
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recurrence in patients with clinical stage I nonseminomatous testicular germ cell tumors and consequences for further follow-up: a single-center 10-year experience.

Abstract: The wait-and-see policy is a reliable method for follow-up monitoring of patients with stage I NSTGCT. Even in patients with unfavorable prognostic factors, it is justified to await the possible appearance of metastases. For the future, it is recommended that CXR be omitted from the schedule, and it might be feasible to discontinue follow-up evaluations after 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
2
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 34 publications
4
78
2
3
Order By: Relevance
“…Approximately 15-30% of patients with stage I NSGCT will relapse with intrathoracic disease [8][9][10][11]. Our series is entirely in keeping with this, with a relapse rate of 19%.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Approximately 15-30% of patients with stage I NSGCT will relapse with intrathoracic disease [8][9][10][11]. Our series is entirely in keeping with this, with a relapse rate of 19%.…”
Section: Discussionsupporting
confidence: 70%
“…Conversely, the risk of not monitoring the chest is that large asymptomatic pulmonary metastases may occur, thereby potentially worsening prognosis and complicating subsequent treatment [16]. In comparison to CT, chest X-ray is generally not considered to be a sensitive method of detecting small pulmonary nodules [11,17]. However, plain chest X-ray can detect pulmonary nodules as small as 5 mm in size depending on location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival outcomes are summarized in Table 5. 13,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The presence of microscopic vascular or lymphatic invasion in the primary tumour is the most important factor predicting relapse and the presence or absence of this factor has been used to divide patients: those with high-risk disease (a third of the cases) who have about a 50% risk of relapse, and those with low-risk disease who have about a 15% to 20% risk of relapse. 45 …”
Section: E25mentioning
confidence: 99%
“…Subsequent studies have shown that vascular invasion (VI) is the single most important prognostic factor regarding risk of relapse [14][15][16][17]. Without adjuvant treatment, the high-risk group (VI positive) has a 3-year relapse rate of approximately 50%, while low-risk patients (VI negative) have a relapse risk of 10 to 20% [1,3,[16][17][18][19][20][21][22].…”
Section: Prognostic Risk Factorsmentioning
confidence: 99%